O Farol de Joana Preta: heterotopia em Olivedos-PB (1940- 1970) - Diniz, Rozeane Porto (2016)
The research aimed to scrutinize the memories relating to "Lighthouse and Joan Black," in Olivedos - PB (1940-1970). Space and commercial sexual exchanges, understand the "Lighthouse" among other settings, as a place and practiced as a heterotopic space deviation from theorists such as Foucault (2001) and Certeau (1994). I made use of the oral method and from there I interviewed eleven people selected according to age and knowledge of the historical facts of Olivedos linked to the Lighthouse and Joan Black. For reasons of memory discussion embasei me in theoretical as Candau (2011), with their ratings of memory and Montenegro (2007), for discussion of orality. The look of the research was guided, in the first chapter to Joan Black discussion as protagonist Lighthouse, historicizing the term "black" and their representations to understand how the name of Joan began to be accompanied by the term in the sense surname. In the second chapter problematizei the identity configurations Joan Francelino Lima, comprising from Hall (2000, p. 108), that identities are "fragmented and fractured," multiple. Also in this chapter, I presented the Joan Black tactics for meeting sexual partners and their encounter with the Catholic Church. In the third chapter, I analyzed the Lighthouse and its representations to Olivedos as "practiced place," multiple and named according to the configuration assigned by popular. In the fourth chapter, I analyzed the historical plot that led to deactivation of the lighthouse at the expense of the Municipality of urbanization process. So the historiographical operation here is woven from the space for discussion, as well as Joan identities as protagonist Lighthouse and representation of the History of Women in Olivedos-PB. Thus, these and other stories about Joan and the Lighthouse will be found here from what makes the historian and will be representations of Paraiba history